Keeping the faith : ordinary people, extraordinary lives : a memoir - Flynt, Wayne, 1940- (Religion & American Culture., 2011)
This historical memoir by the widely recognized scholar, Wayne Flynt, chronicles the inner workings of his academic career at Samford and Auburn Universities, as well as his many contributions to the general history of Alabama. Flynt has traveled the state and the South lecturing and teaching both lay and academic groups, calling on his detailed knowledge of both the history and power structures in Alabama to reveal uncomfortable truths wherever he finds them, whether in academic institutions that fall short of their stated missions, in government and industry leaders who seek and hold power.